2007
DOI: 10.1007/978-1-59745-395-0_12
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Thymic Function Through Quantification of T-Cell Receptor Excision Circles

Abstract: Analysis of immune reconstitution is of major importance in clinical settings such as following bone marrow transplantation or during anti-retroviral treatment of HIV-infected patients. In these patients, thymic function is essential for the reconstitution of a diversified T-cell receptor (TCR) repertoire. During thymopoiesis, several genetic rearrangements lead to the generation of fully functional TCR. By-products of these processes, the T-cell receptor excision circles (TRECs), are present in cells exported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 18 publications
1
64
0
1
Order By: Relevance
“…This shift is thought to mainly result from thymic involution, which is the shrinking in size and function of the thymus that leads to the reduced output of new naïve T cells toward the periphery [16]. Measurement of T-cell receptor excision circle molecules (TREC) expression has been shown to be a reliable marker to assess thymus function [17]. By assessing TREC expression on human peripheral blood mononuclear cells, Sempowski and co-workers showed that the number of naïve T cells drops by 3 orders of magnitude over an 80 year lifespan [18].…”
Section: Age-associated Quantitative and Qualitative Changes In The Cmentioning
confidence: 99%
“…This shift is thought to mainly result from thymic involution, which is the shrinking in size and function of the thymus that leads to the reduced output of new naïve T cells toward the periphery [16]. Measurement of T-cell receptor excision circle molecules (TREC) expression has been shown to be a reliable marker to assess thymus function [17]. By assessing TREC expression on human peripheral blood mononuclear cells, Sempowski and co-workers showed that the number of naïve T cells drops by 3 orders of magnitude over an 80 year lifespan [18].…”
Section: Age-associated Quantitative and Qualitative Changes In The Cmentioning
confidence: 99%
“…sjTRECs are episomal DNA fragments resulting from the deletion of the T cell receptor d region during T cell receptor a locus rearrangement. Because they cannot replicate and are not duplicated, they are diluted out during cell division, allowing a direct evaluation of recent thymic output [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The intracellular TRECs are diluted as the cell proliferates, such that naïve T cells present with relatively high TREC levels, whereas antigen-experienced (memory) T cells have low TREC levels [47]. In the setting of PIDs, TREC evaluation can be used as a diagnostic confirmation of low Fig.…”
Section: T-cell Receptor Excision Circle Quantificationmentioning
confidence: 99%